Effect of pre- and post-inoculation exposure of wheat to high temperature and humidity on spot blotch disease (Bipolaris sorokiniana) - and M.S. PANWAR, V.K. MALIK, D.P. SINGH* (Indian Phytopathology, 2010)
The effect of temperature and relative humidity on development and severity of spot blotch caused by Bipolaris sorokiniana was assessed under artificially inoculated controlled conditions with five isolates by taking susceptible and popular wheat cultivar HD 2329 . The exposure of plants to higher temperature of 35 0C and 95% RH for 24 h at boot leaf stage delayed the appearance of spot blotch symptoms by 6-7 days as compared to those kept at 25 0C and 90% RH. The postinoculation exposure of plants to higher temperature and RH resulted in early development of symptoms by one day in comparison to those exposed before inoculation. The exposure of plants to 35 0C and 95% RH, both at pre- and postinoculation stages reduced the spot blotch score significantly at 18 and 21 days after inoculations as compared to those kept at 25 0C and 90% RH, in case of five isolates and therefore higher temperature is not favourable for spot blotch infection. Amongst five isolates of B. sorokiniana, Bs-4 collected from Karnal was most virulent.